(untitled) (Scientific journal of the Fergana State University, 2024)
For the first time, ichthyological studies of the species composition of the ichthyofauna of the Chodaksoy River, one of the mountain rivers of the Fergana Valley, are being carried out. The article provides information on the species composition of the ichthyofauna of the Chodaksoy River, as well as the morphology, distribution and biology of fish. According to the ichthyological audit of the river, 4 species of fish were discovered. 2 species of fish are considered endemic species, and Oshaninʼs catfish (Glyptosternon oschanini) is included in the number of rare species included in the International Red List and the Red Data Book of Uzbekistan.